Synthesis and Cytotoxic Property of Annonaceous Acetogenin Glycoconjugates - Shi JF; Wu P; Cheng XL; Wei XY; Jiang ZH (Dove Medical Press, 2020)
Jing-Fang Shi,1,2 Ping Wu,2 Xiao-Li Cheng,2 Xiao-Yi Wei,2 Zi-Hua Jiang3 1Guangdong Provincial Key Laboratory for Crop Germplasm Resources Preservation and Utilization, Agro-Biological Gene Research Center, Guangdong Academy of Agricultural Sciences, Guangzhou 510640, People’s Republic of China; 2Key Laboratory of Plant Resources Conservation and Sustainable Utilization, South China Botanical Garden, Chinese Academy of Sciences, Guangzhou 510650, People’s Republic of China; 3Department of Chemistry, Lakehead University, Thunder Bay, Ontario P7B 5E1, CanadaCorrespondence: Zi-Hua JiangDepartment of Chemistry, Lakehead University, 955 Oliver Road, Thunder Bay, Ontario P7B 5E1, CanadaTel +1-807-766-7171Email zjiang@lakeheadu.caXiao-Yi WeiKey Laboratory of Plant Resources Conservation and Sustainable Utilization, South China Botanical Garden, Chinese Academy of Sciences, Xingke Road 723, Tianhe District, Guangzhou 510650, People’s Republic of ChinaTel +86-20-37252538Email wxy@scbg.ac.cnBackground: Annonaceous acetogenins (ACGs) are secondary metabolites produced by the Annonaceae family and display potent anticancer activity against various cancer cell lines. Squamocin and bullatacin are two examples of ACGs that show promising antitumor activity; however, preclinical data are not sufficient partly due to their being highly lipophilic and poorly soluble in water. These compounds also display high toxicity to normal cells. Due to these disadvantageous properties, the therapeutic potential of squamocin and bullatacin as antitumor agents has not been fully evaluated.Methods: In order to enhance their water solubility and potentially improve their cancer targeting, squamocin and bullatacin were conjugated to a glucose or galactose to yield glycosylated derivatives by direct glycosylation or the Cu(I)-catalyzed azide-alkyne 1,3-dipolar cycloaddition (CuAAC) reaction (the click reaction). The synthesized compounds were evaluated for their anticancer property against HeLa, A549 and HepG2 cancer cell lines using MTT assay.Results: Nine glycosyl derivatives were synthesized and structurally characterized. Most of them show comparable in vitro cytotoxicity against HeLa, A549 and HepG2 cancer cell lines as their parent compounds squamocin and bullatacin. It appears that the type of sugar residue (glucose or galactose), the position at which the sugar residue is attached, and whether or not a linking spacer is present do not affect the potency of these derivatives much. The solubility of galactosylated squamocin 13 in phosphate buffer saline (PBS, pH = 7) is greatly improved (1.37 mg/mL) in comparison to squamocin (not detected in PBS).Conclusion: The conjugation of a glucose or galactose to squamocin and bullatacin yields glycosyl derivatives with similar level of anticancer activity in tested cell lines. Further studies are needed to demonstrate whether or not these compounds show reduced toxicity to normal cells and their therapeutic potential as antitumor agents.Keywords: annonaceous acetogenins, squamocin, bullatacin, glycosylated, cytotoxicity, anticancer, solubility